Genetic Diversity Analysis Using Resistance Gene Analog-Based Markers to Support Morphological Characterization of Shallots - Lina Herlina; Reflinur Reflinur; Kristianto Nugroho; Rerenstradika T. Terryana; Sobir Sobir; Awang Maharijaya; Suryo Wiyono (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumber Daya Genetik Pertanian, 2018)
Shallot (Allium cepa var. aggregatum) is one of the most important vegetable crops grown in Indonesia. The limited knowledge available on the genetic diversity and the threat of plant disease have been major problems to maintain high shallot production in Indonesia. Development of molecular markers linked to disease resistance is required for molecular breeding activity in this crop. This study aimed to assess the genetic diversity at conserved domain of resistance gene analog (RGA) in a set of 36 Indonesian shallot genotypes to complement morphological characterization. Twelve morphological and fifteen molecular markers traits were investigated in an attempt to characterize and to discriminate the Indonesian shallots genotypes. Characterization at orphological level indicated that phenotypic variance was highest for total bulb weight (TWB, cv = 99.39%) and the least for the plant height (PH, cv = 28.16%). The correlation analysis between traits showed that TWB and number of bulb (NB), TWB and bulb weight per plant (WB), NB and WB, and WB and PH were positively correlated. Molecular analysis revealed a total of 1,512 alleles with an average of 1.946 alleles per locus. The Polymorphism Information Content (PIC) values ranged from 0.253 to 0.676 and six out of 15 RGA markers were highly informative with PIC values ≥0.50. Based on cluster analysis, the 36 Indonesian shallot genotypes were clearly discriminated into six major groups. These results revealed that the RGA-based markers could support the morphological characterization in evaluating the genetic diversity of shallots.